Сварка и наплавка жаропрочных никелевых сплавов с монокристаллической структурой - Ющенко, К.А.; Задерий, Б.А.; Савченко, В.С.; Звягинцева, А.В.; Гах, И.С.; Карасевская, О.П. (Автоматическая сварка, 2008)
Weldability criteria for heat-resistant single-crystal nickel alloys have been determined. The mechanism has been studied, and causes of cracking have been established, which include deviations of crystallographic orientation of the weld metal from the initial one, and formation of stray grains. The effect of welding parameters and conditions, as well as of crystallographic orientation of welded joints, on the above characteristics has been investigated. Conditions of formation of crack-free welds at minimal mismatching of crystallography and structure of the base and weld metals have been identified.